Analisis Mutu Pelayanan KIA Melalui Peran Kader di Posyandu Mawar Desa Tuntungan I Medan - Yolanda Fidorova; Dinda Febriani (Yayasan Literasi Sains Indonesia, 2023)
Currently, there are still many maternal and child health problems, especially for vulnerable groups, such as groups of pregnant women, breastfeeding, postpartum women and newborns. This is a priority for the government, where the progress of a country is also calculated from the health of mothers and children. A healthy mother will give birth to the next generation of a healthy and productive nation. This study aims to analyze the quality of health services through the role of cadres on maternal and child health at Posyandu Mawar, Tuntungan I Village, Medan, North Sumatra. The method used in this study is descriptive qualitative, which describes the data that has been obtained and uses interview techniques and compares with theories in previous studies obtained from the Google Scholar database. In this study, the results showed that there were 3 roles of cadres in improving maternal and child health, namely socialization, counseling and assistance. The role of cadres in the village has been running smoothly, but researchers found obstacles experienced by cadres in improving the welfare and health of mothers and children. This is due to the lack of community participation in posyandu activities in the village. Thus, more in-depth socialization or counseling is needed so that people's interest can increase and increase their knowledge of maternal and child health.